Student mobility and credit transfer: a case study in Universiti Utara Malaysia (UUM) - M. F. Rajemi,; Hendrik Lamsali,; Herman Shah Anuar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Evolution in the Industrial Revolution has created a new phenomenon not only by industrial player across the board but also has impacted the institution of higher learning. It requires policy makers in the Higher learning institution to be more creative in providing flexible curriculum without compromising the quality of education that they offer. Interestingly, mobility student programme or popularly known as student exchange programme has become one of the central attractions among students. Even though this programme may not be able to be implemented for the whole university due to various reasons, yet, students are still interested to take part in this programme. For them, getting the opportunity to participate in mobility programme would be an added value to their transcript. The opportunity given will expose them to new experience studying abroad for a certain period and increase their graduate employability. This research highlighted a case study done in Universiti Utara Malaysia (UUM). Respondents were among those students who had enrolled in the mobility programme. An innovative credit transfer system for mobility programme has been introduced in UUM. Besides that, strong collaboration between participating institutions (home and host institution) involved in this programme is important to provide effective and beneficial learning environment to students. Findings from this study can be used as a guideline to solve issues on credit transfer system for mobility programme.